IMPLEMENTATION OF DIGITAL INTERACTIVE MULTIMEDIA DEVELOPMENT BASED ON ARTICULATE STORYLINE - Budiana, Sandi; Rostikawati, Teti; Karmila, Nita; Rahmah, Mursidah; Putri, Layli (Universitas Pakuan, 2024)
The research aims to determine the application of developing teaching media by implementing articulatory storylines in learning. Respondents in this study were limited to fourth grade students, the method used was Research and Development by combining the ADDIE model. Feasibility is seen through expert validation, several tests, small group trials, and field trials with indicators of student responses and learning outcomes. The field test was carried out on 40 students. The research results show that digital interactive multimedia and the Articulate Storyline application have great potential for use in learning. Expert validation results obtained an average of 97% with the classification